Investigating the effects of hard anodizing parameters on surface hardness of hard anodized aerospace AL7075-T6 alloy using fuzzy logic approach for fretting fatigue application - Zalnezhad, E.; Sarhan, Ahmed Aly Diaa Mohammed; Hamdi, M. (2013)
Aerospace applications and energy saving strategies in general raised the interest and study in the field of lightweight materials, especially on aluminum alloys. Aluminum alloy itself does not have suitable wear resistance. Therefore, improvements of surface properties are required in practical applications, especially surface hardness when aluminum is in contact with other parts. In this work, first Al7075-T6 was coated using hard anodizing technique in different parameters condition and the surfaces hardness of hard anodizing-coated specimens were measured using microhardness machine. Second, fretting fatigue life of AL7075-T6 was investigated for both uncoated and hard anodized specimens at the highest surface hardness obtained. Third, a fuzzy logic model was established to investigate the effect of hard anodizing parameters, voltage, temperature, solution concentration, and time on the anodized AL7075-T6. Four fuzzy membership functions are allocated to be connected with each input of the model. The results achieved via fuzzy logic model were verified and compared with the experimental result. The result demonstrated settlement between the fuzzy model and experimental results with 95.032 accuracy. The hardness of hard anodizing-coated specimens was increased up to 360 HV, while the hardness of uncoated specimens was 170 HV. The result shows that hard anodizing improved the fretting fatigue life of AL7075-T6 alloy 44 in low-cycle fatigue.